Peran Pendampingan Desa Dalam Implementasi Undang-Undang Desa Di Jawa Tengah -Tahun 2018 - Suharto suharto (LP2M, 2019)
Abstract Village Facilitation is an activity to carry out community empowerment actions through assistance, organization, direction and facilitation of the Village. Village facilitation in the framework of implementing Law Number 6 of 2014 concerning Villages is very important in determining its success. Seeing the current condition of the village which is very heterogeneous in terms of quantity, quality or capacity and even the potential of natural resources and human resources is very varied, the role of village assistance in the framework of implementing the Village Law is very important in helping villages implement the mandate of the Village Law. To find out more about the role of village assistance, in this study the problem is: